From the Paradigm of Learning to the Paradigm of Self-Education: Modern Technologies of Preparation of Students of University of Culture and Arts - Kurgansky, Sergey I.; Turavets, Natalia R.; Vakulenko, Yekaterina G.; Kistenev, Vitalyi V.; Boyko, Kristina Yu. (International Journal of Criminology and Sociology, 2022)
The paper presents the self-education paradigm that takes into account a conscious, focused and rational nature of this phenomenon, substantiates the need to manage this process in the 21st century, considers such concepts in personal development as “to learn” and “to discover”; from the perspective of the organization of the educational process at university, the article studies the correlation of “knowledge” and “education” in the context of self-study of students of universities of culture and arts; it investigates the role and importance of information and communication and time management technologies in students’ self-education.